Maternal Characteristics Mediating the Impact of Household Poverty on the Nutritional Status of Children Under 5 Years of Age in Bangladesh. Issue 3 (September 2021) - Ghosh, Probir Kumar; Das, Pritimoy; Goswam, Doli Rani; Islam, Ausraful; Chowdhury, Sukanta; Mollah, Mohammad Manir; Harun, Golam Dostogir; Akhtar, Zubair; Chowdhury, Fahmida
Objectives: We explored the maternal characteristics that mediate the effect of household poverty on childhood undernutrition. Methods: We used the population-based Bangladesh Demographic Health Survey data from 2014 for demographic characteristics, child and maternal factors. Results: Of the 7173 under-5 children, 3456 (48.2%) had undernutrition. The prevalence of undernutrition was less common in wealthy households (poorest vs richest: adjusted prevalence ratio [aPR] = 1.37), mothers having history of antenatal care (ANC) visits (no visit vs ≥ 4 visits: aPR = 1.22), maternal higher education (no education vs higher education: aPR = 1.54), and mothers with good nutritional status (underweight vs healthy: aPR = 1.13). The risk of undernutrition (37.1%) was attributed to household wealth, mediated 55% by maternal factors; of which 20% by maternal education, 21% by ANC visits, and 14% by maternal nutritional status. Conclusions: Our study findings outlined higher maternal education, ≥ 4 ANC visits and good maternal nutritional status in mediating the impact of household wealth on childhood nutrition.